DESKRIPSI HABITAT KUPU-KUPU - Viva Desi Handayani; I Gede Sugiyanta; Zulkarnain Zulkarnain (JPG (Jurnal Penelitian Geografi), 2013)
The aim of this research was to find out the condition of butterfly habitats in Gita Persada Butterfly Park, Kedaung, Kemiling sub-district, Bandar Lampung, whether the location has been appropriate as the butterfly habitats. This research focused on environmental factors, such as the climate condition (temperature, moisture and precipitation), topography, vegetation, and the diversity of butterfly species. This research used descriptive method, with the objects was Gita Persada Butterfly Park, the width was 4.8 Ha. Respondents in this research was the management and the staff of Gita Persada Butterfly Park. The researcher collected the data using observation interview, and documentation. The obtained data were analyzed and were compared with raw criteria and were interpreted in the research report. The result showed that: ( 1 ) the climate condition of Gita Persada Butterfly Park was C type ( schmidt-ferguson ) with the average rainfall 2087,6 mm / years, as for the temperature was 25,8oc, the moisture was relatively high namely 87,4 %, it was suitable for butterflies habitat. the topography was in the form of highland with a height 460 m dpl, it was suitable for butterfly habitats because the butterfly species will breed at highland topography with the height was 400-1000 m dpl. The condition of vegetation in the open land park were quite many, but the vegetation of host and forage for butterflies in the dome were quite least ( 2 ) the diversity of butterfly species were quite many. Based on the documentation, there were 160 species derived from 5 families which were Papilionidae, Nymphalidae, Pieridae, Lycaenidae and Hesperidae and most of butterflies spesies was conservation came from Nymphalidae families. Keywords: habitat, climate, diversity of butterfly species